Proteomic Changes of Porcine Oocytes After Vitrification and Subsequent in vitro Maturation: A Tandem Mass Tag-Based Quantitative Analysis - Jia, Baoyu; Xiang, Decai; Fu, Xiangwei; Shao, Qingyong; Hong, Qionghua; Quan, Guobo; Wu, Guoquan (Frontiers in Cell and Developmental Biology, 2020)
Cryopreservation of immature germinal vesicle (GV) oocytes is a promising strategy in pigs but still results in reduced oocyte quality due to inevitable cryodamages. Recently there has been a more focus on the molecular changes of oocytes after vitrification, and the alteration in proteome level remains elusive. The aim of this study therefore was to decipher the proteomic characteristics of porcine GV oocytes following to vitrification and in vitro maturation (IVM), using tandem mass tag (TMT)-based quantitative approach and bioinformatics analysis. A total of 4499 proteins were identified, out of which 153 presented significant difference. There were 94 up-regulated and 59 down-regulated proteins expressed differentially in the vitrified oocytes. Functional classification and enrichment analysis revealed that many of these proteins were involved in metabolism, signal transduction, response to stimulus, immune response, complement and coagulation cascades and so on. Moreover, a parallel reaction monitoring technique validated the reliability of TMT data through quantitative analysis for 10 candidate proteins. In conclusion, our results provided a novel perspective of proteomics to comprehend the quality change in the vitrified porcine GV oocytes after IVM.